FINANCIAL INNOVATIONS AND PERFORMANCE OF COMMERCIAL BANKS IN KENYA - Cherotich, Korir Millicent; Sang, William; Mutungú, Charles; Adam Shisia (International Journal of Economics, Commerce and Management, 2015)
Kenya’s banking system has not been exception as far as financial innovations is concerned. The major impetus for financial innovation has been globalization of financial systems, deregulation, and great advances in technologies. The objective of this study was to establish the effect of financial innovations on financial performance of commercial banks in Kenya. This study relied on secondary data. It adopted a census where all the 44 banks were used in the study and there was no sampling since the population size was small. The study found out that there is a strong relationship between financial innovations and financial performance. The study concludes that financial innovations positively affect financial performance. Based on these results, the study recommends that financial innovation information should be available particularly to regulatory and advisory bodies for guidance to the commercial banks on the need to craft and employ sound strategies geared towards continuously embracing innovativeness since innovation leads to improved financial performance. In addition, the study also recommends that firms should create an enabling environment for the employees to be innovative in their operations in order to utilize its competitive advantage so as to increase financial performance and growth of the sector.
Keywords: Financial Innovations; Financial Performance; Commercial Banks; Kenya